2017
DOI: 10.1186/s12917-017-1064-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the fecal bacterial microbiota of healthy and diarrheic foals at two and four weeks of life

Abstract: BackgroundDiarrhea in foals affects up to 60% of foals during the first six months of life. The effect of diarrhea on the fecal bacterial microbiota in foals has not been investigated. Little is known on the fecal bacterial microbial richness and diversity of foals at a young age. The objective was to compare the fecal bacterial microbiota of healthy foals to foals with diarrhea at two and four weeks of life.MethodsFecal samples were collected from foals (n = 20) at 1–14 (T1) and 15–28 (T2) days of age and ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
50
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 41 publications
11
50
0
2
Order By: Relevance
“…Interestingly, similar observations are available for the humans, since indigenous populations seem to have a much broader spectrum of microbiota compared with industrialized countries [104]s horses, seem to be significantly enriched in case of diarrhea and colitis [25,121]. Additionally, foals with diarrhea have shown a less rich microbiome composition in comparison with healthy foals together with decreased abundances for Lachnospiraceae and Ruminococcaceae [122].…”
Section: Current Understanding Of the Equine Microbiomementioning
confidence: 53%
“…Interestingly, similar observations are available for the humans, since indigenous populations seem to have a much broader spectrum of microbiota compared with industrialized countries [104]s horses, seem to be significantly enriched in case of diarrhea and colitis [25,121]. Additionally, foals with diarrhea have shown a less rich microbiome composition in comparison with healthy foals together with decreased abundances for Lachnospiraceae and Ruminococcaceae [122].…”
Section: Current Understanding Of the Equine Microbiomementioning
confidence: 53%
“…In addition to the marked decrease in SCFAs-producing bacteria, significantly low rate of Previous studies have found that potential confounding factors, such as age [33], gender [36], diets [37] and environmental change [38] could impact the bacterial microbiota of differnet body sites.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds are metabolized by enterocytes and have a beneficial role against inflammation in the premature intestine, alter the microbiota, and increase the expression of antiinflammatory cytokines[32]. Streptococcus is an enriched taxon according to LEfSe in the healthy horses[33]. Streptococcus and Lactococcus are negatively correlated with inflammatory parameters (TNF-α, LPS, and H 2 O 2 yield)[34].…”
mentioning
confidence: 99%
“…Dadurch kommt es zu einem Anstieg der Laktatund SCFA-Konzentration sowie zum Abfall des pH-Werts im Dickdarmchymus [25] [32]. Änderungen in der Zusammensetzung dieser komplexen Mikrobiota werden auch bei Erkrankungen wie Kolik [79], Hufrehe [72], Kolitis [9], Grass Sickness [47] und Durchfall [68] beobachtet. Nach jetzigem Forschungsstand ist jedoch unklar, ob diese Veränderungen die Ursache der auftretenden Erkrankung sind oder sich infolge von Schmerz, Stress und Veränderungen der Darmmotilität entwickeln, die mit den beschriebenen Erkrankungen einhergehen [12].…”
Section: Introductionunclassified
“…Die täglich frisch angerührte Kotsuspension sollte 3 Tage lang appliziert werden[56].FazitDie Analyse von Kotproben ermöglicht nur Aussagen über den distalen Abschnitt des Dickdarms beim Pferd[18][42]. Untersuchungen zufolge kommen Vertreter der Bakterienklasse Clostridia, die die größte Bakterienklasse im Dickdarm darstellt, häufiger bei gesunden als bei kranken Pferden vor[9][68]. Hier könnte Potenzial für die Nutzung bestimmter Clostridien-Stämme als Probiotikum liegen.…”
unclassified